ESSENTIAL OILS INHALATIONS IN COMPLEX TREATMENT AND PROPHYLAXIS OF ACUTE RESPIRATORY VIRAL INFECTIONS IN CHILDREN - A. D. Petrushina; A. S. Nikogosyan; I. D. Kaib; L. A. Mal'chenko; S. A. Ushakova (Вопросы современной педиатрии, 2012)
The prevalence of respiratory tract infections in children of the Russian Federation is high. That is why the questions of prophylaxis and treatment of acute respiratory viral infections (ARVI) are always of a great interest of paediatricians. During epidemic outbreaks essential oils inhalations become a new perspective in treatment of such conditions. In the period of time since September 2011 till February 2012 the research workers of Paediatrics department of Tyumen State Medical Academy have estimated the oil «Dyshi» («Breathe») efficacy in complex treatment of ARVI in children. The usage of this medicine for the prophylaxis of respiratory infectionsdecreased the morbidity rate to 35% during the observation period, while each child in the comparison group had at least one episode of ARVI. The usage of this drug in the group of frequently ill children at the first symptoms of ARVI allowed to relieve the severity of disease and to prevent complications. Furthermore, the oil «Dyshi» has a number of other advantages: it is not irritating and habit-forming, it does not dry the nasal mucous membrane, it is safe for children and can be used for a long period of time.